Mucocutaneous Ulcerations and Pancytopenia Secondary to Methotrexate Toxicity in a Patient With Rheumatoid Arthritis: A Case Report - Thinley Dorji; Tshering Penjor; Sangay Tenzin; Tshering Pedon; Sangay Wangchuck; Sonam Yangchen (Clinical Case Reports)
ABSTRACT Toxicity from methotrexate overdosing is life threatening condition that requires prompt recognition and early treatment. A 71‐year‐old man from rural Bhutan with diabetes mellitus had symmetrical small joint pain for 3 years associated with early morning stiffness. He was evaluated and diagnosed with seropositive rheumatoid arthritis in a hospital in neighbouring India. He was initiated on Methotrexate and Hydroxychloroquine. The patient had inadvertently taken Methotrexate 10 mg OD for 2 weeks. Following this, he developed painful ulcers on the lips preventing him from swallowing and ulcers around the corona on the penis. He also had intermittent fever with chills. On examination, he had fluid responsive hypotension and pancytopenia without bleeding manifestations. He was managed with intravenous folinic acid, subcutaneous granulocyte colony stimulating factor and intravenous cloxacillin. He had an uneventful recovery and methotrexate has been restarted following adequate patient education. Education of patient and family members is key in preventing medication errors. Early identification and timely management of methotrexate toxicity is key in preventing mortality.